Bio‐ethylene from sugarcane as a competitiveness strategy for the Brazilian chemical industry. (9th December 2019) - Oliveira, Camilla C.N.; Rochedo, Pedro R.R.; Bhardwaj, Rajat; Worrell, Ernst; Szklo, Alexandre
Abstract: The urgency with which the world economy needs to be decarbonized could lead to the emergence of regions with the capacity to produce renewable feedstock such as biomass. The competitiveness of these regions could result from their ability to produce high value‐added chemicals at the lowest cost. The biomass embodied in a chemical product could reduce carbon emissions, leading to net CO2 removal. The aim of this study was to test the hypothesis that bio‐ethylene could make the Brazilian chemical industry more competitive. This would be achieved by applying the revenues from carbon credits associated with using ethanol and sugarcane bagasse as feedstocks for bio‐ethylene production. Three production routes were compared according to their estimated cost of production in Brazil under a simplified life‐cycle analysis: sugar‐cane‐derived ethanol to ethylene (with and without CO2 capture and storage – BECCS); bio‐methanol to olefin; and conventional steam cracking of naphtha. When associated with the production of long‐lasting materials, the ethanol‐to‐ethylene with BECCS route achieved the lower CO2 break‐even price (US$75/t CO2 ), followed by ethanol to ethylene without BECCS (US$82/t CO2 ) and bio‐methanol to ethylene (US$106/t CO2 ). Our findings highlight the advantage for the Brazilian chemical industry of implementing a national or, even better, a global carbon‐pricing instrument. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd